Risk Factors and Scoring Systems for Patients with Candidemia at a Tertiary Hospital in Jakarta, Indonesia - Mursinah Mursinah; Fera Ibrahim; Mardiastuti H Wahid (Acta Medica Indonesiana)
Aim: to identify the risk factors of candidemia and to develop a scoring system that could be implemented in Cipto Mangunkusumo Hospital (RSCM), Jakarta, Indonesia. Methods: this study was a retrospective study with case control design using the medical records of patients since 2011 to 2014. All sepsis patients hospitalized in the RSCM with a positive blood culture for Candida were included in this study as a case group. The control group was all of the sepsis patients without candidemia. The ratio for case and control groups was equal (1:1). Results: from 234 patients who were analyzed, the risk factors that influenced the study were length of stay of 8-14 days (OR 3.464; 95% CI 1.458-7.800), length of stay of more than 14 days (OR 6.844; 95% CI 3.0-15.330), severe sepsis (OR 16.407; 95% CI 1.458-7.800), and surgery (OR 3.03; 95% CI 1.492-6.152). The predictors for candidemia in RSCM were length of stay in hospital for 8-14 days (score 1), a length of stay ≥14 days (score 2), severe sepsis (score 3), and surgery (score 1), with a cut off score of 3.5. Conclusion: the results of this study have indicated that a scoring system in order to guide an empirical treatment for candidemia can be developed by using the risk factors for candidemia from patients who have been identified as patients with risk at Cipto Mangunkusumo Hospital.